ENHANCING SPEAKING SKILLS THROUGH THE USE OF SHADOWING TECHNIQUE: AN EXPERIMENTAL STUDY - Darmawan, Darmawan; Sindi, Sindi; Wahyudin, Wahyudin; Marhum, Mochtar (TELL - US JOURNAL, 2025)
This research aims to investigate the effect of the shadowing technique on improving the speaking skills of eleventh-grade students at SMA Negeri 2 Palu, particularly in terms of accuracy and comprehensibility. Shadowing is a learning method that involves listening to and immediately repeating the speech of a native speaker to develop natural pronunciation, intonation, and sentence structure. This study used a pre-experimental design with a one-group pre-test and post-test model. The subjects were 27 eleventh-grade students selected through purposive sampling. The research instrument was an oral speaking test that focused on two assessment aspects: accuracy and comprehensibility. The results showed an increase in the students’ average score from 42.12 in the pre-test to 62.03 in the post-test. The hypothesis testing using a t-test revealed that the t-count value (3.936) was higher than the t-table value (1.706) at a 0.05 significance level, indicating that the hypothesis was accepted. This means that the shadowing technique was effective in improving students’ speaking skills, especially in helping them overcome difficulties in pronunciation, grammar, and vocabulary. Based on these findings, the shadowing technique can be considered an effective and interactive strategy for teaching speaking in English language classrooms.